The CD151‐midkine pathway regulates the immune microenvironment in inflammatory breast cancer. Issue 1 (24th March 2020) - Hayward, Steven; Gachehiladze, Mariam; Badr, Nahla; Andrijes, Regina; Molostvov, Guerman; Paniushkina, Liliia; Sopikova, Barbora; Slobodová, Zuzana; Mgebrishvili, Giorgi; Sharma, Nisha; Horimoto, Yoshiya; Burg, Dominic; et al.
Abstract: The immune microenvironment in inflammatory breast cancer (IBC) is poorly characterised, and molecular and cellular pathways that control accumulation of various immune cells in IBC tissues remain largely unknown. Here, we discovered a novel pathway linking the expression of the tetraspanin protein CD151 in tumour cells with increased accumulation of macrophages in cancerous tissues. It is notable that elevated expression of CD151 and a higher number of tumour‐infiltrating macrophages correlated with better patient responses to chemotherapy. Accordingly, CD151‐expressing IBC xenografts were characterised by the increased infiltration of macrophages. In vitro migration experiments demonstrated that CD151 stimulates the chemoattractive potential of IBC cells for monocytes via mechanisms involving midkine (a heparin‐binding growth factor), integrin α6β1, and production of extracellular vesicles (EVs). Profiling of chemokines secreted by IBC cells demonstrated that CD151 increases production of midkine. Purified midkine specifically stimulated migration of monocytes, but not other immune cells. Further experiments demonstrated that the chemoattractive potential of IBC‐derived EVs is blocked by anti‐midkine antibodies. These results demonstrate for the first time that changes in the expression of a tetraspanin protein by tumour cells can affect the formation of the immune microenvironment by modulating recruitment of effector cells to cancerous tissues. Therefore, a CD151‐midkine pathway can be considered as a novel target for controlled changes of the immune landscape in IBC. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.